Evaluation of MRI Features and Neurodevelopmental Outcomes for Prenatally Diagnosed Periventricular Pseudocysts - Sun, Cong; Zhang, Xinjuan; Chen, Xin; Wei, Xinhong; Chen, Yufan; Yang, Aocai; Zhu, Jinxia; Wang, Guangbin (Frontiers in Pediatrics, 2021)
Objectives: This study aimed to evaluate the morphologic features and neurodevelopmental outcomes of individuals prenatally diagnosed with a periventricular pseudocyst (PVPC). Methods: Pregnant women with a fetus prenatally diagnosed with PVPC by MRI were enrolled in this retrospective study. The fetuses with PVPCs were divided into group 1 (isolated PVPC) and group 2 (PVPC with additional findings). The surviving infants underwent brain MRI examinations and the Gesell Developmental Scale (GDS) test after birth. Independent sample t-tests were used to compare the differences in the developmental quotient (DQ) between group 1 and group 2. We also analyzed the correlations among the DQ, location (unilateral/bilateral), size (diameter), and number (single/multiple) of the PVPCs in group 1 using Lasso regression. Results: In total, 131 infants (group 1: 78 infants, group 2: 53 infants) underwent MRI examinations after birth, and 97 infants (group 1: 59 infants, group 2: 38 infants) underwent the GDS test. Upon follow-up, the sizes of the cysts had become smaller or disappeared after birth. The average DQ in group 2 was lower than that in group 1 (all with p < 0.001). In group 1, the location (unilateral/bilateral), size (diameter), and number (single/multiple) of the PVPC did not affect the DQ. Conclusions: The PVPCs became smaller or disappeared after birth. Isolated PVPCs usually have a normal presentation after birth regardless of the location, number, or size. For PVPCs with additional findings, the neurodevelopmental outcomes were inferior to those in isolated PVPCs.